Editorial: co‐morbid gastrointestinal conditions are an important consideration in IBS management. Issue 10 (21st April 2021) - Simons, Madison; Taft, Tiffany H.
Abstract : LINKED CONTENT This article is linked to Black et al and Black & Ford papers. To view these articles, visit https://doi.org/10.1111/apt.16322 and https://doi.org/10.1111/apt.16351